Bibliometric Analysis of Consumer Behavior in Sustainable Fashion: Trends, Insights, and Future Direction - Aiyya Nadira Fairuz Zahra; Nur Kholifah (Sean Institute, 2026)
Consumers are becoming increasingly aware of the environmental and social impacts of their purchasing choices, prompting in-depth research into consumer behavior in sustainable fashion. This study analyzes research trends in consumer behavior in sustainable fashion using bibliometric methods to identify key topics, patterns of researcher collaboration, and future research directions. Using a PRISMA-based systematic literature review methodology, data from 514 publications (2015-2025) were downloaded from Scopus and analyzed in RStudio using the Bibliometrix package to visualize citation networks, author collaborations, and keyword trends. Results revealed three dominant topics: “Sustainability” (192 publications), “Sustainable Fashion” (112 publications), and “Consumption Behavior” (109 publications), with an annual growth rate of 27.91%. International collaboration reached 26.26%, with significant contributions from leading universities such as Yonsei University and Sapienza Università di Roma, as well as institutions from the United States, Italy, and China. In conclusion, although understanding of consumer behavior in sustainable fashion has grown rapidly, future research should prioritize circular economy models, the influence of social media, consumer willingness to pay, and the adoption of sustainable consumption patterns in developing countries to drive the fashion industry's transition towards global sustainability.